POLITICAL CONSCIOUSNESS AND ITS PERCEPTION - Ibodulla Kungirov (Scholar Express Journal, 2023)
In the development of a democratic state, the level of spiritual and spiritual world and political awareness of citizens is of great importance. Therefore, improving the political consciousness of citizens, further activating their participation in democratic processes, is considered one of the priority tasks. Because a citizen with a formed political consciousness has a high political faith, who understands the country's peace, social development, interests and needs of his nation and is able to maintain national harmony and national cohesion. This article describes the formation of the political consciousness of citizens, its characteristics, and its reaction to the political events taking place in society. Also, the connection of political consciousness with social practice and the relationship to social-political processes in society are summarized on a scientific and creative basis.
Keywords: Democratic state; political consciousness; political processes